Fatigue, interoplastic and nociplastic distress in myalgic encephalomyelitis/chronic fatigue syndrome, Gulf War Illness, and chronic idiopathic fatigue - Chen, Emily; Rudder, Tamera; Nwankwere, Charles; Baraniuk, James N. (Frontiers in Neuroscience, 2025)
IntroductionMyalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) and Gulf War Illness (GWI) have similar profiles of pain (nociception), visceral interoception, and tenderness (central sensitization) that may be due to dysfunction of midbrain and medulla descending antinociceptive and antiinteroceptive mechanisms. If so, then dolorimetry, a proxy for tenderness, may be correlated with subjective symptoms. The relationship with fatigue was assessed in Chronic Idiopathic Fatigue (CIF).MethodsCohorts of ME/CFS, GWI, and sedentary control subjects completed questionnaires and had dolorimetry. Spearman correlations were calculated between central sensitization (dolorimetry), fatigue (Chalder Fatigue), pain (McGill Pain), interoception (Chronic Multisymptom Inventory), disability (SF36), psychological constructs, and other symptoms. Females were more tender than males and were thus analyzed separately.ResultsGWI and ME/CFS groups were more tender than controls for females (p < 0.0045) and males (p < 10−6). Receiver operating characteristics area under the curve for female ME/CFS (0.730) and GWI (0.792) and male ME/CFS (0.816) and GWI (0.831) were not optimal for diagnostic purposes. Pain and interoception were highly correlated. Dolorimetry correlated better with pain (Spearman R = −0.574 to −0.629) than interoception (R = −0.417 to −0.545) questionnaires. Dolorimetry correlated weakly with fatigue and disability (|R| < 0.42). CIF was defined by receiver operating characteristics with elevated fatigue, postexertional malaise, and reduced vitality. CIF had intermediate tenderness.DiscussionThe outcomes generate several hypotheses about ME/CFS and GWI pathophysiology. Disease pathologies may involve injury to midbrain and medulla regulatory pathways causing central sensitization with the loss of descending antiinteroceptive and antinociceptive inhibitory mechanisms and increased perceptions of widespread visceral complaints and pain. The diseases can be re-conceptualized as chronic disabling fatigue with heightened interoceptive and nociceptive symptoms. Variations in antiinteroceptive control may provoke unpredictable shifts in symptom spectrum and severity that contribute to exertional exhaustion and symptom exacerbation. Subjective criteria were found to define CIF prospectively.